Concepts of Actionability in Precision Oncology. - Chin-Yee, Benjamin; Plutynski, Anya (Philosophy of Science, 2024)
"Actionability" is a key concept in precision oncology. Its precise definition, however, remains contested. This article undertakes a philosophical analysis of "actionability" to aid in conceptual clarification. We map distinct concepts of actionability, arguing that each is best understood as a contextually objective category articulated to mitigate risk of "conceptual slippage." We defend "interactive pluralism," acknowledging the need for distinct concepts but also for conceptual interaction in practice. This article thus offers insights for both practitioners and philosophers, clarifying approaches to actionability for scientists and clinicians and serving as a case study to test competing views on scientific pluralism.